Investigation Into Prevalece Of Escherichia coli Infection And Some Other Diseases In Broiler Farms In Sulaimani District: Jalal M. Shareef and Nahla M. Saeed - Shareef, Jalal M. (The Iraqi Journal of Veterinary Medicine, 2005)
In regard to broiler diseases in Sulaimani district, different factors likeenvironmental temperature, humidity, wind velocity, the source of hatchery eggsand day-old chicks were studied. The study involved the history, someconcurrent diseases, methods of protection against viral diseases, clinical signs,post mortem lesions, isolation and identification methods (cultural andbiochemical) and sensitivity test. The 4th and 5th weeks ages were theexposed ages for respiratory diseases, precisely Escherichia coli infection. Thetemperature factor (high and low) was among the most prominent predisposingfactors, since 39% and 30% of E.coli isolates obtained through winter andsummer seasons successively. The low environmental temperature (5.2˚C)accompanied by high humidity rate (72.3 %), caused high number of infections.The high temperature (32.6 ˚C), with lower rate of humidity (26.2%); has alsoincreased the number of infections. Field investigation including 12 monthssurvey was conducted in the present work. The survey involved 1256 batchesfrom broiler farms, which involved (11,564,385) chicks. A total of 946 (75%)batches showed respiratory signs, including 709 E.coli infected batches. Otherinfections by Salmonella and Proteus were also discovered. The sensitivitytest of 200 E.coli isolates revealed that 165, 156 and 118 isolates were sensitiveto ciprofloxacine, gentamycin and chloromphenecol respectively. While 182,181, and 175 isolates were resistant to flumequine, ampcillin and lincomycinconsecutively.